Pedicle versus free flap reconstruction in patients receiving intraoperative brachytherapy. Issue 4 (3rd July 2016) - Geiger, Erik J.; Basques, Bryce A.; Chang, Christopher C.; Son, Yung; Sasaki, Clarence T.; McGregor, Andrew; Ariyan, Stephan; Narayan, Deepak
Abstract: Introduction This study compared complication rates between pedicle flaps and free flaps used for resurfacing of intraoperative brachytherapy (IOBT) implants placed following head and neck tumour extirpation to help clarify the ideal reconstructive procedure for this scenario.Patients and methods A retrospective review of reconstructions with IOBT at our institution was conducted. Patient and treatment details were recorded, as were the number and type of flap complications, including re-operations. Logistic regressions compared complications between flap groups.Results Fifty free flaps and 55 pedicle flaps were included. On multivariate analysis, free flap reconstruction with IOBT was significantly associated with both an increased risk of having any flap complication (OR = 2.9, p = 0.037) and with need for operative revision (OR = 3.5, p = 0.048) compared to pedicle flap reconstruction.Conclusions In the setting of IOBT, free flaps are associated with an increased risk of having complications and requiring operative revisions.